AGILE as a particle detector: Magnetospheric measurements of 10–100 MeV electrons in L shells less than 1.2. Issue 4 (23rd April 2016) - Argan, A.; Piano, G.; Tavani, M.; Trois, A.
Abstract: We study the capability of the AGILE gamma ray space mission in detecting magnetospheric particles (mostly electrons) in the energy range 10–100 MeV. Our measurements focus on the inner magnetic shells with L ≲ 1 . 2 in the magnetic equator. The instrument characteristics and a quasi‐equatorial orbit of ∼500 km altitude make it possible to address several important properties of the particle populations in the inner magnetosphere. We review the on board trigger logic and study the acceptance of the AGILE instrument for particle detection. We find that the AGILE effective geometric factor (acceptance) is R ≃50 cm 2  sr for particle energies in the range 10–100 MeV. Particle event reconstruction allows to determine the particle pitch angle with the local magnetic field with good accuracy. We obtain the pitch angle distributions for both the AGILE "pointing" phase (July 2007 to October 2009) and the "spinning" phase (November 2009 to present). In spinning mode, the whole range (0–180 degrees) is accessible every 7 min. We find a pitch angle distribution of the "dumbbell" type with a prominent depression near α = 90° which is typical of wave‐particle resonant scattering and precipitation in the inner magnetosphere. Most importantly, we show that AGILE is not affected by solar particle precipitation events in the magnetosphere. The satellite trajectory intersects magnetic shells in a quite narrow range ( 1 . 0 ≲ L ≲ 1 . 2 ); AGILE then has a high exposure to a magnetospheric region potentially rich of interesting phenomena. The large particle acceptance in the 10–100 MeV range, the pitch angle determination capability, the L shell exposure, and the solar‐free background make AGILE a unique instrument for measuring steady and transient particle events in the inner magnetosphere. Key Points: AGILE has the currently largest particle acceptance for 10–100 MeV electrons in the inner belt with L approximately less than 1.2 Measurement of the pitch angle distribution and particle flux which is unaffected by solar activity Detection of a stable "dumbbell" pitch angle distribution for high‐energy electrons and positrons in the inner magnetosphere